Mental Workload Analysis of Workers Using the Swedish Occupational Fatigue Index (SOFI) Method at A Job Shop, Sheet Metal, And Pipe Metal Manufacturing Company in Surabaya - Mochammad Tutuk Safirin; Mega Islami; Rizqi Sari; Sinta Dewi; Enny Aryanny (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This study aims to determine the mental workload of 15 respondents at PT. X in the morning shift and night shift, as measured by the Swedish Occupational Fatigue Index (SOFI) method. The highest value of the morning shift fatigue index dimension is found in the lack of energy factor with a value of 3.97, while in the night shift, the highest value is in the sleepiness factor with a value of 3.13. The fatigue index of workers is considered to be still high and work system improvements are needed.